THE ALTERED VOLATILITY SPILLOVER SEQUENCE UNDER COVID-19: INDIAN SECTORAL INDICES IMPACT DEIBOLD YILMAZ INDEX - Tomar, Kunwar Sanjay (Indian Journal of Finance and Banking, 2022)
The Industrial sectors have their unique place in the economic interlinkage. The sectoral valuation reflected by each sector indices shows how each sector responds to different events. The exogenous event Covid-19 impact has been differential due to the impact of lockdown and other Covid-19 appropriate restrictive measures. The present paper examines the change in the volatility spillover induced by Covid-19. The study uses daily sectoral indices data from India’s oldest exchange, the Bombay Stock Exchange. Data from January 2010 to November 2020 has been split into four subgroups to find how COVID-19 has affected the volatility spillover using the Diebold and Yilmaz Index. Ranks have been assigned to find the change in the four periods’ volatility to the volatility spillover’s magnitude and direction. The impact of the COVID-19 is strong enough to change the volatility spillover, which followed a system. Capital Goods volatility increased three times. At the same time, the Auto sector becomes a volatility receiver instead of the net volatility dispenser, from 2.5% before COVID-19 to -3.39% after COVID-19 lockdown. Bankex remains unaffected by Covid-19. JEL Classification Codes: G01, G11, D81, D85.